EFFECT OF THE MONOMERS RATIO IN THE ELECTROSYNTHESIS OF POLY(ANILINE-CO-O-METHOXYANILINE) ON STEEL CORROSION PROTECTION - Ramírez, Andres Mauricio; del Valle , María Angelica; Motheo , Artur; Mieres, Florencia (Journal of the Chilean Chemical Society, 2020)
In this work, the synthesis of poly(aniline-co-o-methoxyaniline) was carried out on AISI 304 steel, by voltammetric or potentiostatic method. Electropolymerization was achieved from different ratios of 0.4 mol·L-1 aniline/o-methoxyaniline monomers in 1.0 mol·L-1 H2SO4. Homo- and copolymers were characterized by cyclic voltammetry, infrared spectroscopy, and scanning electron microscopy. Furthermore, the electrodeposits were studied with a view to their use as corrosion protectors, for which their polarization curve was measured in NaCl 3% and, after 168 h, the surface of the steel was also evaluated by optical microscopy. It was observed that the reactivity that the o-methoxy group gives to the aniline ring reduces the protection against corrosion due to the excessive inclusion of N-phenyl-1,4-benzo quinone-di-imine oligomers and/or with an oxazine structure. On the other hand, the optical images confirm the surface damage of the steel, correlating with SEM images that show morphological changes associated with the progress of synthesis and the o-methoxy group. Nevertheless, under optimal conditions, poly(aniline-co-o-methoxyaniline) modifies the corrosion potential of AISI 304 steel, displacing it by 0.283 V. Furthermore, the presence of small pits and the absence of surface oxide was observed, indicating a significant delay in the oxidation of AISI-304 steel.